Barreiras para o crescimento de empresas de base tecnológica do setor de tecnologia da informação e comunicação em Ribeirão Preto - SP - Bomfim, Eliza Maria da Cunha (Universidade Federal de São Carlos, 2017)
This research aims to identify and analyze the barriers to the growth of companies from Information and Communication Technology sector in Ribeirão Preto, seeking to identify alternatives to improve the sustainability and performance of these companies. As a theoretical guideline, the perspectives of Resource Based View and Resource Dependency Theory were addressed, as well as the concepts of factors relevant to the growth of the organizations pointed out in the literature. To this end, a triangulation of methods was adopted, with a qualitative and quantitative approaches, with interviews with five experts from the ICT sector and a survey with technology-based companies based in the metropolitan area of ​​Ribeirão Preto. The survey was carried out using a Likert scale questionnaire applied to a sample of 30 technology-based companies, drawn from 70 ICT companies located in that region. For the data treatment, the techniques of descriptive statistics as well as Principal Component Analysis and Regression Analysis were used to identify what affects a company's billing, with the proposition of two hypotheses. Also for the analysis of the opinions of the specialists was made the content analysis. The questionnaire evaluated 33 growth factors (variables), distributed in six categories: internal barriers related to the individual; internal barriers related to organization; external barriers related to government policies; external barriers related to educational quality; external barriers related to technological infrastructure; external barriers related to the business environment. The results indicate that the barriers to the growth of ICT companies in this region are mainly focused on the low qualification of professionals, and the lack of public incentives and the lack of integration between companies in the sector and universities in the search for the strengthening of the entrepreneurial ICT ecosystem in that region. Finally, in order to counter the barriers presented, the solution pointed out by the entrepreneurs is the cooperation between private companies in order to create joint alternatives to the problems common to all, and, ultimately, to pressure the public power to make the necessary changes. It became clear, therefore, that the entrepreneurial ICT ecosystem in the Ribeirão Preto region still has much to evolve and conquer, but the initiatives are being organized and the future is promising.
Barriers to growth of technology-based companies in the information and communication technology sector in Ribeirão Preto - SP
Keywords: Barreiras para crescimento das organizações; Empresa de base tecnológica; Tecnologia da Informação e Comunicação; Barriers to the growth of organizations; Technology-based company; ENGENHARIAS::ENGENHARIA DE PRODUCAO